2010
DOI: 10.1007/s10464-009-9283-3
|View full text |Cite|
|
Sign up to set email alerts
|

Healing Men and Community: Predictors of Outcome in a Men's Initiatory and Support Organization

Abstract: Men have poorer health and declining social outcomes when compared to women, and research suggests that behaviors related to restrictive and traditional male gender roles contribute to this disparity. This study is an examination of The ManKind Project International (MKPI), a community-based organization that provides alternative male gender norms and a community support system to help reinforce them. The MKPI runs an intensive, experiential "Training Adventure Weekend" (TAW), followed by voluntary, on-going p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…This, coupled with men’s greater propensity to be in groups that drink alcohol during or after meetings (69% of men versus 34% of women in the current study), suggests that community groups are often used by men, not as a means to protect their family, but as a way to develop and demonstrate their masculine identities – often at the expense of their health. Acknowledging social constructions of masculinity as a barrier to health and well-being, growing efforts are being made to document the pathways through which men can create social spaces to renegotiate and develop more health-enabling masculinities (Barker and Ricardo, 2005, Colvin and Robins, 2009, Burke et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with men’s greater propensity to be in groups that drink alcohol during or after meetings (69% of men versus 34% of women in the current study), suggests that community groups are often used by men, not as a means to protect their family, but as a way to develop and demonstrate their masculine identities – often at the expense of their health. Acknowledging social constructions of masculinity as a barrier to health and well-being, growing efforts are being made to document the pathways through which men can create social spaces to renegotiate and develop more health-enabling masculinities (Barker and Ricardo, 2005, Colvin and Robins, 2009, Burke et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Specific negotiation strategies are described that serve either to avoid anti-gay violence, live up to expected images of masculinity, or create unique images of personhood free of gender role expectations. Finally, Burke et al (2010) examine change over time and the factors that predict change in primarily middle class men who participate in a male support organization, ManKind Project International (MKPI). The sample as a whole reported decreased levels of gender role conflict and depression symptoms, and enhanced life satisfaction following involvement in an intensive ''initiation'' weekend.…”
Section: Notementioning
confidence: 99%
“…15-17). More recently, several evaluations of one peer-led men's mutual help organization, the Mankind Project (MKP), have indicated that participation is associated with reduced gender role conflict and increased well being (Anderson, Maton, Burke, Mankowski, & Stapleton, 2014;Burke, Maton, Mankowski, & Anderson, 2010;Maton, Mankowski, Anderson, Barton, Karp, & Ratjen, 2014).…”
Section: Self-help Organizational and Group Characteristics Of Mkpmentioning
confidence: 99%